Performance analysis of massive MIMO receivers - Fernandes, Daniel Filipe Sobral (2017)
We face now an exponential increase in wireless devices and to allow good user experience, it is imperative that the next generation of mobile (5G) communications ensures reliable connections, high data transfer rates and low latency. One way to increase the data transfer rate is to use massive Multiple-Input, Multiple-Output (MIMO) systems, that is, systems with multiple antennas to emit and multiple antennas to receive thus allowing spatial diversity. In these systems, to increase the battery life of the devices it is preferable to use the Single-Carrier with Frequency-Domain Equalization modulation in the uplink as this modulation reduces the complexity in the emitter, transferring it to the receiver, in this case the Base Staion, where it is quite acceptable. This dissertation studies the performance of massive MIMO receiver systems, comparing it to the performance achieved with the Matched Filter Bound (MFB). The Iterative Block Decision-Feedback Equalizer (IB-DFE) receiver presents a very similar performance to the MFB, however, the algorithm requires matrix inversions, which in the systems under study, where the size of the matrix is high, implies an increase of the associated operations increases. Thus it is very important that low complexity receivers, such as the Maximal-Ratio Combining (MRC) or Equal Gain Combining are used. In this dissertation, a simple receiver is proposed combining the IB-DFE receiver with the MRC receiver, thus creating a low complexity receiver with excellent performance